Virtue ethics and professional roles / Justin Oakley, Dean Cocking. - Oakley, Justin, 1960-; Cocking, Dean, 1958- (Cambridge University Press, 2001)
Professionals, it is said, have no use for simple lists of virtues and vices. The complexities and constraints of professional roles create peculiar moral demands on the people who occupy them, and traits that are vices in ordinary life are praised as virtues in the context of professional roles. Should this disturb us, or is it naive to presume that things should be otherwise? Taking medical and legal practice as key examples, Justin Oakley and Dean Cocking develop a rigorous articulation and defence of virtue ethics, contrasting it with other types of character-based ethical theories and showing that it offers a promising new approach to the ethics of professional roles. They provide insights into the central notions of professional detachment, professional integrity, and moral character in professional life, and demonstrate how a virtue-based approach can help us better understand what ethical professional-client relationships would be like.